An ostracode crustacean with soft parts from the Lower Silurian. - Siveter, D; Sutton, MD; Briggs, D; Siveter, D (2003)
An exceptionally well-preserved ostracode from the Silurian of Herefordshire, United Kingdom, provides a rare view of the fossilized soft-part anatomy of this important group of living crustaceans and confirms that Ostracoda were extant in the Paleozoic. The fossil has striking similarity to the extant myodocopid family Cylindroleberididae, to which it is assigned, and demonstrates remarkable evolutionary stasis over 425 million years. The fossil is identified as a male on the basis of its copulatory organ.